2019
DOI: 10.1093/bib/bbz050
|View full text |Cite
|
Sign up to set email alerts
|

PRISMOID: a comprehensive 3D structure database for post-translational modifications and mutations with functional impact

Abstract: Post-translational modifications (PTMs) play very important roles in various cell signaling pathways and biological process. Due to PTMs’ extremely important roles, many major PTMs have been studied, while the functional and mechanical characterization of major PTMs is well documented in several databases. However, most currently available databases mainly focus on protein sequences, while the real 3D structures of PTMs have been largely ignored. Therefore, studies of PTMs 3D structural signatures have been se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 58 publications
0
26
0
Order By: Relevance
“…It should be noted that we tried a large number of other types of features generated by iLearn [36] or Pse-in-One [37] toolkits when we designed the input features (data not shown). The sequence-based features generated by these two toolkits have been used widely for predicting both RNA post-transcriptional modification sites [38][39][40] and post-translational modification sites [41,42]. Our experimental results demonstrated that our proposed feature combination in this study yielded satisfactory performance, which cannot be significantly improved when they were combined with other features.…”
Section: Discussionmentioning
confidence: 89%
“…It should be noted that we tried a large number of other types of features generated by iLearn [36] or Pse-in-One [37] toolkits when we designed the input features (data not shown). The sequence-based features generated by these two toolkits have been used widely for predicting both RNA post-transcriptional modification sites [38][39][40] and post-translational modification sites [41,42]. Our experimental results demonstrated that our proposed feature combination in this study yielded satisfactory performance, which cannot be significantly improved when they were combined with other features.…”
Section: Discussionmentioning
confidence: 89%
“…2) It combined various meta-predictors via the SVM-based Collaborative Learning. It can be anticipated that the proposed Collaborative Learning framework would be applied to solve many important problems in bioinformatics, such as protein disordered protein prediction [64], DNA replication origin prediction, protein post-translational modification sites [65], etc.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that we tried a large number of other types of features generated by iLearn [ 36 ] or Pse-in-One [ 37 ] toolkits when we designed the input features (data not shown). The sequence-based features generated by these two toolkits have been used widely for predicting both RNA post-transcriptional modification sites [ 38 – 40 ] and post-translational modification sites [ 41 , 42 ]. Our experimental results demonstrated that our proposed feature combination in this study yielded satisfactory performance, which cannot be significantly improved when they were combined with other features.…”
Section: Discussionmentioning
confidence: 99%